Grain Sorghum Cost-Return Budget in Northeast Kansas - Dhuyvetter, Kevin C. (My University, 1999)
This publication projects a budget that reflects expected income and costs based on grain sorghum production in northeastern Kansas.
MF573_1999_10
Keywords: MF573; Economics; Crops; MF